An Electrostatically Actuated MEMS Arch Band-Pass Filter - Hassen M. Ouakad (Shock and Vibration)
This work presents an investigation of the dynamics of micromachined arches resonators and their potential to be utilized as band-pass filters. The arches are actuated by a DC electrostatic load superimposed to an AC harmonic load. The dynamic response of the arch is studied analytically using a Galerkin-based reduced-order model when excited near its fundamental and third natural frequencies. Several simulation results are presented demonstrating interesting jumps and snap-through behavior of the arches and their attractive features for uses as band-pass filters, such as their sharp roll-off from pass bands to stop bands and their flat response.